Intercultural conversation - Cheng, Winnie (Pragmatics & beyond, 2003)
This innovative study of naturally-occurring English conversations between Hong Kong Chinese and their native English friends and colleagues makes a worthwhile contribution to the research literature on intercultural conversation. Through analyzing dyadic intercultural conversations, the study investigates the ways in which culturally divergent conversationalists manage their organizational and interpersonal aspects of the unfolding conversations. The study focuses on five features of conversational interaction -- disagreements, compliments and compliment responses, simultaneous talk, discourse.